Ischemic fasciitis in a debilitated older man. Issue 3 (3rd July 2019) - Gavin, Meredith; Sharp, Leigha; Atkins, Randy; Tarbox, Michelle
Abstract: We present the rare case of ischemic fasciitis in an elderly man with a history of Parkinson's disease. The patient presented with multiple subcutaneous masses on his lower back, ranging in size from 3 to 8 cm. Histopathologic evaluation showed areas of deep dermal and subcutaneous fibrinoid necrosis with granulation tissue-like vessels as well as reactive fibroblasts. The histopathologic presentation as well as the clinical presentation confirmed ischemic fasciitis as the etiology. Ischemic fasciitis, also called atypical decubital fibroplasia, is a rare entity characterized by a reactive, nonneoplastic proliferation of atypical fibroblasts. Though a benign pseudosarcoma, it is often confused with a sarcoma due to their similar clinical and histological presentation. Recognition of this distinct benign entity is essential to avoid misdiagnosis.